The population of Veneto faced with technological consumption of music during the pandemic - De Moya Martínez, María del Valle; Segura Tornero, Alfredo; Casabon, Cedric Marc Alain; Hernández Bravo, José Antonio (Frontiers in Psychology, 2024)
Objective This work is the result of one of the lines of research opened in the LabinTic group (UCLM) and a stay in the city of Padua, in the Italian Veneto area, in 2022. After observing the side effects in Italy as a result of COVID-19 and the Great Lockdown, we wanted to know in more depth some aspects related to how the people of Veneto used IT as an important weapon to fight against forced isolation and, if possible, compare this with other similar studies performed in Castilla-La Mancha. Method To achieve this objective, an ad hoc questionnaire was designed and validated through expert judgment. This questionnaire was administered to a random probabilistic sample by disseminating it through social media and email using the “snowball” method. A total of 338 people who comprised the population sample of the study (n = 338) were obtained. After analyzing the data through SPSS 28, using a mixed methodology considering qualitative and quantitative aspects, the great influence that IT had among the Italian population during the lockdown common aspects of their everyday lives and incorporating some acquired habits (listening to music, for example) into their usual life routines after the return to normality was determined among other features and assessments. In summary, the text highlights how the pandemic influenced music consumption, the popularity of different music genres, the role of social media, and the enduring importance of the music itself in people’s lives. It suggests that music remains a source of comfort and entertainment in challenging times.